Occurrence of twig blight and branch dieback of walnut caused by Botryosphaeriaceae species in Turkey - Ayhan Yildiz; Seher Benlioglu; Kemal Benlioglu; Yunus Korkom (Journal of Plant Diseases and Protection, 2022)

The molecular detection of Fusarium oxysporum f. sp. dianthi races in protected carnation growing areas in western Turkey - Ceren Cer; Seher Benlioglu; Yesim Egerci (Journal of Plant Diseases and Protection, 2022)

Effects of soil amendments combined with solarization on the soil microbial community in strawberry cultivation using quantitative real-time PCR - Umit Ozyilmaz; Kemal Benlioglu; Ayhan Yildiz; H. Seher Benlioglu (Phytoparasitica, 2016)

Globally invading populations of the fungal plant pathogen V erticillium dahliae are dominated by multiple divergent lineages - Dylan P. G. Short; Suraj Gurung; Pierre Gladieux; Patrik Inderbitzin; Zahi K. Atallah; Franco Nigro; Guoqing Li; Seher Benlioglu; Krishna V. Subbarao (Environmental Microbiology, 2015)
Summary The spread of aggressive fungal pathogens into previously non‐endemic regions is a major threat to plant health and food security. Analyses of the spatial and genetic structure of plant pathogens offer valuable insights into their origin, dispersal mechanisms and evolution, and have been useful to develop successful disease management strategies. Here, we elucidated the genetic diversity, population structure and demographic history of worldwide invasion of the ascomycete V erticillium dahliae , a soil‐borne pathogen, using a global collection of 1100 isolates from multiple plant hosts and countries. Seven well‐differentiated genetic clusters were revealed through discriminant analysis of principal components ( DAPC ), but no strong associations between these clusters and host/geographic origin of isolates were found. Analyses of clonal evolutionary relationships among multilocus genotypes with the e BURST algorithm and analyses of genetic distances revealed that genetic clusters represented several ancient evolutionary lineages with broad geographic distribution and wide host range. Comparison of different scenarios of demographic history using approximate B ayesian computations revealed the branching order among the different genetic clusters and lineages. The different lineages may represent incipient species, and this raises questions with respect to their evolutionary origin and the factors allowing their maintenance in the same areas and same hosts without evidence of admixture between them. Based on the above findings and the biology of V . dahliae , we conclude that anthropogenic movement has played an important role in spreading V . dahliae lineages. Our findings have implications for the development of management strategies such as quarantine measures and crop resistance breeding.

Soil disinfestation options in Aydın province, Turkey, strawberry cultivation - Seher Benlioglu; Ayhan Yildiz; Özhan Boz; Kemal Benlioglu (Phytoparasitica, 2014)